9+6(-4n-2)=-2(-5+2)-8

Simple and best practice solution for 9+6(-4n-2)=-2(-5+2)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+6(-4n-2)=-2(-5+2)-8 equation:


Simplifying
9 + 6(-4n + -2) = -2(-5 + 2) + -8

Reorder the terms:
9 + 6(-2 + -4n) = -2(-5 + 2) + -8
9 + (-2 * 6 + -4n * 6) = -2(-5 + 2) + -8
9 + (-12 + -24n) = -2(-5 + 2) + -8

Combine like terms: 9 + -12 = -3
-3 + -24n = -2(-5 + 2) + -8

Combine like terms: -5 + 2 = -3
-3 + -24n = -2(-3) + -8

Multiply -2 * -3
-3 + -24n = 6 + -8

Combine like terms: 6 + -8 = -2
-3 + -24n = -2

Solving
-3 + -24n = -2

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -24n = -2 + 3

Combine like terms: -3 + 3 = 0
0 + -24n = -2 + 3
-24n = -2 + 3

Combine like terms: -2 + 3 = 1
-24n = 1

Divide each side by '-24'.
n = -0.04166666667

Simplifying
n = -0.04166666667

See similar equations:

| 2x=(3/2-x) | | 7e-7=60.2 | | 14+4x=-7+12x | | 14+4x=12x-7 | | 4x+14=12x-7 | | 9x-4=11x-10 | | 5(a+3)=45 | | 27=-3(6) | | (1/3)(y+17)=3y-5(y-3) | | 9=7c-5 | | 12x-7=4x+14 | | 5.3x+1=3.8x-11 | | 2(3x-6.5)=20 | | (3x-8)+(2x+5)-(4x-8)= | | 5/13=x/8 | | 3x+1.4=x+1.8 | | 54/x=-6 | | 6-9x=-57 | | 4-3x=-8x+14 | | 5x=x+0.8 | | 35.4=-6g | | 2(z-4)+3z=4-(z+2) | | -7v+5v=-2-8 | | 11x=60.5 | | 4-3x=8x+14 | | 7y-10-5y+5=0 | | z-5z=-4 | | -(5x+2)=8 | | -2x+15=-17 | | 4u=-7 | | 44*.5= | | 3x^2-23x+13=0 |

Equations solver categories